Macleod's clinical examination - Britton, Robert; Danielson, Ethan (Elsevier Ltd., 2018)
This classic textbook aims to assist clinicians develop the consultation skills required to elicit a clear history, and the practical skills needed to detect clinical signs of disease. Where possible, the physical basis of clinical signs is explained to aid understanding. Formulation of a differential diagnosis from the information gained is introduced, and the logical initial investigations are included for each system